An analysis of the modern approach to the evaluation of vagueness at calibration of measuring facilities of gas expense and amount - Бродин, Ю. І.; Бродин, З. М. (METHODS AND DEVICES OF QUALITY CONTROL, 2009)
European experience of analysis of vagueness, general approaches and differences which exist in different documents in relation to the analysis of vagueness at measuring of charges and gas amount, come into a question. The analysis of the modern state of application is carried out in Ukraine of the European going near the evaluation of vagueness at calibrations of facilities of measuring of expense and gas amount